Integrating Assessment Tools and Practices in EFL Classrooms: A Multidimensional Approach Aligned with CEFR Standards - ZA, Asep Ahmad; Ratmo (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2025)
This study critically examines the evolving role of assessment and evaluation in Teaching English as a Foreign Language (EFL), emphasizing a paradigm shift from summative judgment to a continuous, formative process integral to instruction. Through qualitative content analysis of theoretical literature and practical frameworks, the research synthesizes multidimensional assessment practices that align with the Common European Framework of Reference for Languages (CEFR). It explores diverse assessment tools—including written exams, oral tests, multiple-choice questions, performance tasks, checklists, and analytic rubrics—and evaluates their efficacy in measuring integrated language skills (listening, speaking, reading, writing). Findings reveal that imbalances in skill development often stem from isolated assessment methods, leading to communicative inadequacies (e.g., comprehension without production). The study advocates for contextually authentic, CEFR-aligned strategies that bridge receptive and productive competencies, such as combining reading with written responses or listening with oral tasks. Additionally, it underscores the distinction between assessment (systematic observation) and evaluation (criterion-referenced judgment), highlighting the need for balanced tool selection to enhance reliability and reduce anxiety. Practical implications include leveraging checklists for skill-specific benchmarks, analytic rubrics for performance clarity, and iterative feedback for writing development. The research concludes that holistic, integrated assessment designs are essential for fostering balanced language proficiency and achieving meaningful educational outcomes in global EFL contexts.